2020
DOI: 10.1001/jamainternmed.2020.3989
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Physicians’ Electrocardiogram Interpretations

Abstract: STUDY SELECTION Of 1138 articles initially identified, 78 studies that assessed the accuracy of physicians' or medical students' ECG interpretations in a test setting were selected.DATA EXTRACTION AND SYNTHESIS Data on study purpose, participants, assessment features, and outcomes were abstracted, and methodological quality was appraised with the Medical Education Research Study Quality Instrument. Results were pooled using random-effects meta-analysis. MAIN OUTCOMES AND MEASURES Accuracy of ECG interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 110 publications
0
71
0
2
Order By: Relevance
“…In different populations, it was observed that, after training, improvement was less than expected. 9 According to the study conducted by Khanna et al, a statistically significant difference was observed in the interpretation of the definitive diagnosis, with a 14 % increase after the educational intervention. However, no differences were observed in our cohort regarding the ability to determine if an ECG was normal or abnormal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In different populations, it was observed that, after training, improvement was less than expected. 9 According to the study conducted by Khanna et al, a statistically significant difference was observed in the interpretation of the definitive diagnosis, with a 14 % increase after the educational intervention. However, no differences were observed in our cohort regarding the ability to determine if an ECG was normal or abnormal.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have described that ECG interpretation is limited both among physicians and medical students. [4][5][6][7][8][9] In addition; multiple residency programs do not offer formal ECG interpretation training. 5 Pediatricians are often the first health care providers to assess children with a potential c a r d i a c p a t h o l o g y .…”
Section: Introductionmentioning
confidence: 99%
“…En las distintas poblaciones, se observó que, luego del entrenamiento, la mejoría obtenida era menor que la esperada. 9 Conforme con el estudio de Khanna et al, se mostró una diferencia estadísticamente significativa en la interpretación del diagnóstico de certeza con un aumento del 14 % luego de la intervención educacional. Sin embargo, en nuestra cohorte, no se hallaron diferencias en cuanto a la capacidad de reconocer si un electrocardiograma era normal o anormal.…”
Section: Discussionunclassified
“…E s t u d i o s r e c i e n t e s d e s c r i b e n q u e l a interpretación del electrocardiograma es limitada tanto en médicos como en estudiantes de Medicina. [4][5][6][7][8][9] Además, múltiples programas de residencias no cuentan con entrenamiento formal en dicha habilidad. 5 Los pediatras son, frecuentemente, los primeros agentes de salud en evaluar a un niño con posible patología cardíaca.…”
Section: Introductionunclassified
“…7 Over the past two decades, the lack of ECG competence has been well described for medical students, [8][9][10][11] residents, [12][13][14][15][16][17][18][19][20] and quali ed clinicians worldwide. [21][22][23][24][25][26] Undergraduate [27][28][29] and postgraduate ECG curricula [30][31][32][33][34][35] have been proposed in an attempt to standardise training in electrocardiography. However, to the best of our knowledge, exposure to the ECGs recommended by these curricular guidelines has not previously been reported for clinical clerkships or residency programmes.…”
Section: Introductionmentioning
confidence: 99%